Design Factors and Energy Cost of Restaurant Operations in a North-Central Region of the USA - Hyung-Chan, Kim; Hwang, Joyce H. (My University, 2010)
According to the sustainable passive solar design theory, design factors including building orientation, size of window, and location of window are related to energy consumption. Based on this theory, design factors such as a proportion of windows, orientation of window, and building orientations were empirically tested in their relationship to energy cost of a restaurant. LEED® for Commercial Interiors indicated that this approach not only made a positive impact on public health and the environment, it also reduced operating costs and enhanced building and organizational marketability. The purpose of this study was to identify design factors that are related to energy consumption using actual operation's data of family restaurants in a north-central region. Restaurants located in the north central region in the U.S spent larger proportion of their operating expenses on energy. Family style restaurants were selected because they have similar kitchen equipment and seating allowance. Construction document was acquired to gather size of operations and other design factors. Scatter plots and correlation analysis were used to examine relationships between design factors and energy consumption in each restaurant. Among the five family style restaurant operations in a north-central region that participated in this study, the size varied from 2810 square feet to 9138 square feet. Energy cost per cubic foot was then calculated using adjusted energy cost and total cubic footage of each restaurant. The building orientation did not show close relationship with energy consumption of restaurants. However, the proportion of south window indicated a negative relationship to the energy consumption. The findings of this study were based on 5 restaurants and thus there is a need for another study with bigger sample size to verify these findings. In addition, similar studies in different climate regions will be beneficial in testing the passive solar design theory in restaurant operations.
Keywords: Interior design; Sustainable design